Influences of Yield Strength and Section Depth to the Compression Capacity of Single Cold-Formed Channel Lipped - Tan, Boon Kai; Shek, Poi Ngian; Ahmad Kueh, Beng Hong (IOP Publishing, 2019)
This paper presents a parametric study on single cold-formed channel lipped section subject to axial compression load. The aim of this study is to investigate the influences of yield strength and depth of the section towards the compression capacity of a thin channel section. The study started with the calculation of effective area of a channel section followed by the calculation of compression capacity in accordance to BS EN 1993-1-1. The capacity of the section is then checked with experimental results for validation purpose. Parametric study is conducted to investigate the relationship between the yield strength, section depth and compression capacity. It is concluded that increment in yield strength tend to reduce the effective area of a thin channel section. On the other hand, the increment in section depth has a very little influence to the effective area of a cold-formed channel lipped section.